DETERMINANTS OF ASSETS GROWTH OF FOREIGN OWNED BANKS IN INDONESIA - Aswin Rivai; Rina Indiastuti (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
The aim of this research is to assess the dominant factors enabling foreign owned banks to increase their assets in Indonesia and to confirm whether the “follow the customers hypothesis” is also applicable in motivating foreign owned banks to do business in Indonesia to support investment and trade activities of the companies originated from foreign countries. Using the panel data of 28 foreign owned commercial banks in Indonesia between 2006-2015 obtained from Indonesian Banking Directory, Indonesian Banking Statistics databases, foreign country central bank websites, a least square dummy variable (LSDV) regression model was applied to examine the effect of Bilateral Trade, Foreign Direct Investment (FDI), Interest Rate Differences, Domestic Deposits, Parent banks Return on Assets (ROA) and Length of Time presence of the foreign owned banks in Indonesia on Assets or Size of Foreign Owned Banks. The main findings is that the decisions by foreign owned banks to operate and to expand its business in Indonesia is predominantly affected by the increase in realization of projects funded by Foreign Direct Investment from counterpart countries, third parties fund or domestic deposit denominated in foreign currencies, profitability of the parent banks in home country and long time presence in Indonesia to enable parent bank and their branches or subsidiaries gain better operating experience, better general managerial expertise and better knowledge of local environment. Bilateral Trade and Interest Rate Differences between home and host country has no impacts at all on Assets of Foreign Owned Banks. “Follow the customer hypothesis” is applicable in Indonesia only in terms of FDIs but not applicable in terms of bilateral trade. The findings will help management of the banks in designing more reliable business plan and also used as input or tools for policy makers prior issuing the license for the newly open foreign owned banks offices or increase of its branch offices. It is suggested foreign owned banks to consider empowering its trade financing scheme which will increase the banks size or assets.